Images of Arabs and Islam in Burton’s Pilgrimage to Al-Madinah and Meccah - Alseadoon, Abdulkarim Mohammad; Nash, Geoffrey (Arab Journal for Sciences and Research Publishing, 2023)
The study aimed to discuss the position of Arabs and Islam in Western culture, concentrating on the British Victorians whose main conception of Arabia concerned the desert and the exotic orient. The increasing political and economic interest of the British government in Arabia led to more focus on Muslim Arabs in the Near East and the Arabian Peninsula, beginning with Napoleon’s conquest of Egypt c. 1799, and escalating as Suez and the Ottoman Empire became more intertwined with the British imperialism. Missions and tours for various reasons went to the Near East and the Arabian Peninsula to discover and bring information for the Western Empires specially, the Royal Geographical Society. On the other hand, the growing body of science concerning the Arab world came under the umbrella of orientalism, including all writers, novelists and travelogues concerned with ‘the orient’. One of the oriental travellers was Burton, whose mission to visit the two Islamic holy places Al-Madinah and Mecca was a classic and romantic one. Burton’s mission was not only to supply his sponsors with geographical and scientific information about Suez, the Arabian Peninsula and the two holy places, but he had other personal motivations that affected his work; Personal Narrative of A Pilgrimage to Al-Madinah and Meccah. Continuously, the study applies investigative, descriptive analysis and critical analysis methods to answer the above questions. The study consists of four sections. Section one presents an introduction in five subsections: problem of the study, hypotheses of the study, significance of the study, methodology of the study and finally, structure of the study. Section two presents Victorians’ views of Muslims in three subsections: Victorian thinking and culture in Britain; Islam in the Victorian literature; and Victorian travelogues. Section three comprises a thematic analysis of Burton’s Pilgrimage, concentrating on his liberal and ethnographic interests that motivated his imperialism. At the last section, the study discusses the final results, the study limitations and recommendations for the studies about Burton.